Triple jump online - Sorenson, S.
Triple Jump Online has been created in order to provide an internet resource serving all aspects of the event as well as its related topics. My name is Shawn Sorenson, and I am a junior triple jumper from Rice University in Houston, Texas, USA. Since I am also a long jumper, this page contains quite a bit of information on the LJ, as well as Track & Field in general. As a student of the sport as well as an athlete, an area of great interest to me is Track & Field Biomechanics. Biomechanics is the study of how the laws of physics and physiology interact with motion of living things. As a senior at Eureka High School (Eureka, CA), I began a research project involving the biomechanical analysis of the horizontal jumping events, namely Long and Triple Jump. This project is one which I have continued during my time at Rice, and may continue into graduate school. You can check out my research project under the Biomechanics section of this page, although most of my recent work has not yet been posted there. This page is intended to be a resource to all people involved in related areas of Triple Jumping, Track & Field, and Science. If you have any suggestions, comments, or contributions that you feel you could make to this page, please e-mail me at riceroo@rice.edu. Also, please check out the Jumper's Network section. One of the objectives of this page is to serve as a reference point and central location for jumpers/coaches/scientists/spectators to exchange ideas and resources. As of September 25, 1997, Kangaroo's TJ Online is now hosting a Media Archive of Triple and Long Jump Photos & Video. Again, this is intended as a resource, and visitors are encouraged to use and contribute to this section.